Effects of personality trait, motivation factors on performance of customer service personnel (CSP): a case of MPH bookstores - Yahaya, Azizi (Academic Journals, 2011)
Staff performance has been discussed widely and endlessly. Several theories have been used in order to measure performance. Previous research found that personality and motivation showed a significant relationship towards staff performance. The objective of this study is to investigate which type of personality among Big 5 personality traits could be a predictor of staff performance and also which level of Maslow’s theory contributed most towards performance. Questionnaires have been distributed to eight departments in Head Office and twelve outlets around Kuala Lumpur and Klang Valley. Results showed that extroversion, agreeableness, conscientiousness and openness to experience are positively correlated with performance, while social, self-esteem and self-actualization correlate positively with performance. The result shows that the three predictors of extrovert (Beta = 0.505; t = 7.661; Sig = 0.001), agreeableness (Beta = 0.219; t = 0.3475; Sig = 0.001), social (Beta = 0.143; t = 2.551; Sig = 0.013) and conscientiousness (Beta = 0.143; t = -0.136; Sig = 0.013) accounted for 34.4% increase in change in job satisfaction. MPH also does not forget a person with an agreeableness type of personality trait. However, organization should not consider the conscientious character. In terms of motivation, social need is the predictor for performance of the staff.